Room temperature gas-solid reaction of titanium on glass surfaces forming a very low resistivity layer - Solís Sánchez, Hugo (2016)
Titanium films were deposited on quartz, glass, polyamide and PET substrates in a high vacuum system at room temperature and their electrical resistance monitored in vacuo as a function of thickness. These measurements indicate that a low electrical resistance layer is formed in a gas-solid reaction during the condensation of the initial layers of Ti on glass and quartz substrates. Layers begin to show relative low electrical resistance at around 21 nm for glass and 9nm for quartz. Samples deposited on polyamide and PET do not show this low resistance feature.